MENTE: Terminal year end reports - Mackun, Dylan Jonah T. (Animo Repository, 2023)
MENTE is a partnership comprised of aspiring student entrepreneurs, Mr. Kenneth Eufracio, Ms. Taryn Espiritu, Mr. Dylan Mackun, Mr. Evan Nelle, and Ms. Angelika Turda. The business sought to provide people with a more convenient and satisfying coffee experience through coffee drips and other ingredients that give a richer taste to coffee. In doing so, MENTE distributed five (5) products to the market during its business operations. MENTE first distributed Bean Boxes in two flavors which are the Mocha coffee kit and the Latte coffee kit. Later on, the business added diversified products which are Mocha Syrup kit, Latte syrup kit, and coffee drip pouch. MENTE used locally sourced materials such as Arabica coffee beans produced in the country in order to be part of the support for the domestic economy. The MENTE Terminal Year-End Report (TYER) narrates, in a substantial yet direct way, the outcomes of the business and the experiences of the partners throughout the course program. Chapter one (1) of the TYER outlines MENTE’s highlights of the performance which are the objectives they set and were able to achieve. The first chapter also details how MENTE strategized on its strengths, weaknesses, opportunities, and threats. The partners contemplated their setbacks and how they pushed forward to lead the different departments with the management team which is discussed further in the second chapter of the TYER. Chapter three (3) is a more quantitative analysis of the business by comparing the different planned targets with the actual targets met. Succeedingly, chapter three of the TYER points out the success factors, best practices, challenges, and actions of MENTE for each department. What bears fruit from all those is also the significant learning the partners had which they convey in Chapter 4. With CSR activities, the partners also gave back to the communities, as shown in chapter five. Lastly, each member’s future plans are shared in chapter six of the TYER. The partners did not continue the business but plan to use their learnings for their forthcoming ventures.